Association of Energy Adequacy with 28-Day Mortality in Mechanically Ventilated Critically Ill - BİLGİLİ, BELİZ; CİNEL, İSMAİL HAKKI (GALENOS YAYINCILIK, 2019)
Objective: This study investigates the relationship of nutritional risk status with 28-day mortality in critically ill. Materials and Methods: This retrospective study included critically ill adult patients receiving >48 hours receiving mechanical ventilation. Data on baseline characteristics and the modified Nutritional Risk in Critically ill (mNUTRIC) score were collected on day 1. Energy intake was recorded daily until death, discharge or until twelfth evaluable days. Patients were divided into 2 groups: a) received <75% of prescribed energy, b) received >= 75% of prescribed energy. Results: One hundred and fifty patients were included in the study. Patients with <75% of prescribed energy intake had longer length of ICU stay, duration of mechanical ventilation (p<0.001) and higher 28-day mortality (p<0.001). In the multi-logistic regression analysis, BMI (OR 0.87, CI 0.85-0.95, p<0.001) and mNUTRIC score (OR 2.3, CI 1.4-2.93, p<0.001) were associated with 28-day mortality. In subgroup analysis, the decrease in daily energy intake was associated with an increase in 28-day mortality in patients with a high mNUTRIC score (high mNUTRIC score OR 1.65, CI 1.20-1.70, p<0.001), but this relationship was not observed in the low mNUTRIC score group. Conclusion: The mNUTRIC score is associated with 28-day mortality in mechanically ventilated critically ill. In patients with a high mNUTRIC score, receiving 05% of the prescribed energy may positively affect patient outcomes.
Keywords: Nutrition; mortality; mNUTRIC score; NUTRITION SUPPORT THERAPY; CARE MEDICINE SCCM; ENTERAL NUTRITION; AMERICAN SOCIETY; PATIENT SOCIETY; CALORIC-INTAKE; GUIDELINES; MULTICENTER; PROVISION